INOVASI KUALITAS PELAYANAN PUBLIK PEMERINTAH DAERAH - Robi Cahyadi Kurniawan (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
AbstractPublic service is a measure of the performance of the government's most visible. Communities can directly assess the government's performance based on the service they received. For the quality of public services in all ministries / institutions is a fundamental thing that must be improved. Improved public services, the Ministry of Administrative Reform and Bureaucratic Reform policy that since 2014 was a year of public service innovation. All government agencies, both at central and local levels is expected to make a creative idea or an answer to how to work / public service method. Ministry of Administrative Reform and Bureaucratic Reform collect and assess the innovations that have been made in a number of agencies across Indonesia. Hopefully the quality and innovation of public services BPS can always be increased, so that it can continue to compete fairly with other agencies. Keywords: Innovation, Public Services, Local Government AbstrakPelayanan publik merupakan suatu tolok ukur kinerja pemerintah yang paling kasat mata. Masyarakat dapat menilai langsung kinerja pemerintah berdasarkan pelayanan yang diterimanya. Untuk itu kualitas pelayanan publik di semua kementerian/lembaga adalah suatu hal yang mendasar yang harus segera ditingkatkan. Peningkatan pelayanan publik, Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi (KemenPAN RB) menerapkan kebijakan bahwa sejak tahun 2014 adalah tahun inovasi pelayanan publik. Seluruh instansi pemerintah, baik di pusat maupun daerah diharapkan dapat membuat suatu ide kreatif atau jawaban terhadap cara kerja/metode pelayanan publik. KemenPAN RB mengumpulkan dan menilai inovasi-inovasi yang telah dilakukan di sejumlah instansi di seluruh Indonesia. Semoga kualitas dan inovasi pelayanan publik BPS dapat selalu meningkat, sehingga bisa terus bersaing secara sehat dengan instansi lain. Kata Kunci: Inovasi, Pelayanan Publik, Pemerintah Daerah